Food Agriculture Supply Chains during a Pandemic - Hanissa Okitasari; Puji Handayani Kasih; Yasmin Mauliddina; Yunita Nugrahaini Safrudin (Universitas Pendidikan Indonesia, 2021)
Nowdays COVID-19 (Coronavirus) pandemic has affected almost all countries and has made an effect on the global supply chain in general and food agricultural supply chain in specific. The effect of this pandemic can be cluster by time period as the initial blockade period and as the later period of the pandemic. This new condition made us to pay attention about what differences before, during, and after the pandemic that will occur. The aim of this research are to know not only during the pandemic, but also what may be happen after the pandemic, especially on food agriculture supply chain. In this research we use literature study method which there are 9 articles has been reviewed. We find out that this pandemic not to significantly affect the structure of food agricultural supply chain, but there is a possibility to shorten the food agricultural supply chain if needed.